Islamization Of Knowledge In Qur’anic Perspective - M. Thoriqul Islam; Elvan Tedio Fawaz (Universitas Darussalam Gontor, 2017)
Islamization is a discipline that describes the form of the character and Islamic identity as a way of life or worldview in which there is an integral view of the concept of knowledge (epistemology) and the concept of God (theology). In Islam, knowledge is formed and sourced from the Islamic view of life, which is closely related to the basic structure of the metaphysics of Islam that has formulated in-line with revelation, tradition, reason, experience and intuition. Formation of those through the educational process. However, due to the influence of western worldview through westernization and globalization, Islamic education lost its role in linking science with Islamic view of life. Therefore, the muslim scholars, among others, Ismail al-Faruqi in his